Mislabelling of nicotine content in electronic cigarette liquids in Malaysia: implications on public health - Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Draman, Samsul; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Rahman, Azizur; Syed, Mahmood; Jamshed, Shazia Qasim (Medical Malaysia Association, 2017)
Electronic cigarette (e-cig) is a battery-operated device which vaporises nicotine solution into a form of inhalable aerosol. The level of nicotine in the liquid for e-cig (e-liquid) may vary and the typical nicotine concentration reported is between 6 to 24 mg of per ml. Based on the National Electronic Cigarette Survey (NECS) 2016, 83.9% of e-cig adult users in Malaysia preferred eliquid with 6 mg/ml nicotine. In Malaysia, nicotine in products other than tobacco is regulated under the Poisons Act 1952, restricting its sale by licensed health professionals only. However, the sale of e-liquid containing nicotine is widespread and vapers are not assured of the accuracy of content versus that on the label of the e-liquid bottle. OBJECTIVE: To determine the actual nicotine concentration in selected e-liquid brands marketed in Malaysia. Methods: Samples (81 brands) obtained from respondents of the NECS 2016 were analysed using gas chromatography mass spectrometry (GC-MS) in selective ion mode (SIM) at a certified laboratory. Results: 15 samples labelled as no or zero nicotine were found to contain nicotine. Nine samples contained level of nicotine higher than what their labels indicated. Interestingly, 57 samples had nicotine concentrations that were lower than that indicated on the labels. The nicotine concentration percentage difference between labelled and result from analysis was found to be as low as from -99.16% to -1.28% in 64 samples, while in 4 samples the difference was higher; 0.083% to 163.0%, and the remaining 13 samples had no mention of nicotine concentration on their labels. Conclusion: Significant discrepancy was detected in nicotine concentration between the labelled and analysed values among the collected e-liquid samples. Strict regulation and enforcement is needed for e-cig liquids to ensure safety of users and compliance to current regulations on nicotine.